Greek-Romanian Symbiotic Patterns in the Early Modern Period: History,Mentalities, Institutions - I - Panou, Nikos (The Historical Review/La Revue Historique, 2007)
The patriarchal decree validating the establishment of the Wallachian archdiocese in 1359; a series of documents pertaining to the early history of the Koutloumousiou monastery on Mount Athos; the surviving redactions of Patriarch Niphon II's lost vita; the proceedings of the interrogation of a Greek priest arrested by the Polish authorities on charges of conspiracy and espionage; and an emphatically digressive section in Matthew of Myra's verse chronicle known as History of Wallachia. This article, of which the first part is presently published, offers a discussion of these textual materials - which span four crucial centuries of Balkan history and represent an intriguing variety of discursive practices and traditions. It aims to contribute to a deeper understanding of the intricate mechanisms that generated a climate of toleration, mobility and inter-ethnic contact in the Ottoman Balkans, enabling a symbiotic relationship between Greeks and Romanians, which found its vital space in the semi-autonomous and strategically located Danubian principalities, and endured throughout the early modern period despite having been severely undermined by opposing tendencies and conflicting interests. The two sections at hand focus on the Bishop of Myra's pivotal text, as well as on written records related to the early, and yet formative, contacts between the nascent Romanian states and the late Byzantine Empire; in the two remaining sections, which will appear in the next volume of The Historical Review, this endeavour will be brought to a conclusion by means of a (necessarily selective) presentation of evidence dating from the period after the fall of Constantinople and up to the beginning of the seventeenth century.